Pengaruh Social Media Influencer dan Credibility of Influencer terhadap Perceived Quality dan Purchase Intention (Studi Kasus Influencer TikTok Codeblue) - Mohamad Yanwar Habibi; Diah Ayu Kusumawati (Lembaga Yasin AlSys, 2026)
Although the role of social media influencers has received increasing attention in digital marketing research, studies that specifically examine the relationship among influencer presence, credibility of influencer, perceived quality, and purchase intention in the context of food review content on TikTok remain limited. This study aims to analyze the influence of social media influencer and credibility of influencer on purchase intention, with perceived quality as a mediating variable. This study employed a quantitative approach with a survey design involving 100 respondents who were followers of the TikTok influencer Codeblue and were selected through purposive sampling. Data were collected through a questionnaire and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results showed that social media influencer and credibility of influencer had a significant effect on perceived quality. In addition, perceived quality was proven to have a significant effect on purchase intention and to mediate the relationship between influencer and consumers’ purchase intention. These findings contribute to the development of signaling theory and the digital marketing literature by expanding understanding of how influencer credibility and social media content shape perceived quality and consumer purchasing behavior. The study concludes that perceived quality is an important factor in shaping purchase intention through influencer-based marketing activities. Therefore, companies and digital marketers are advised to collaborate with influencers who have high credibility and to present informative content to strengthen consumers’ perceptions of product quality. The implications of this study include theoretical contributions to the influencer marketing literature and practical implications for business actors in optimizing marketing strategies through social media.